2016
DOI: 10.1088/1748-9326/11/6/064019
|View full text |Cite
|
Sign up to set email alerts
|

The changing influences of the AMO and PDO on the decadal variation of the Santa Ana winds

Abstract: Santa Ana wind (SAW) events have great implications for the environment of Southern California, but the cause of their decadal variability has not been fully understood. We show with observational analysis that the Atlantic multi-decadal oscillation (AMO) has a stronger influence than the Pacific decadal oscillation (PDO) in modulating SAW activity through two mechanisms: the Great Basin pressure gradient mechanism, in which a strengthened Great Basin high promotes SAW activity and vice versa through the north… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 32 publications
2
21
1
Order By: Relevance
“…The second largest change in cluster frequency for the SC domain occurs in cluster 6, which is 2.3% less frequent by end-of-century. The synoptic fields for these days is depicted in Figure 11, and corresponds to a typical wind pattern from Santa Ana events (Raphael, 2003;Westerling et al, 2004;Li et al, 2016;Millstein et al, 2019;Guzman-Morales and Gershunov, 2019). The relatively high 700hPa geopotential height field over the western US, along with the high center sitting off-shore, leads to the northeasterly wind field throughout the SC region.…”
Section: Sc 6: Less Frequent and Weaker Santa Ana Winds In Fall/wintermentioning
confidence: 94%
“…The second largest change in cluster frequency for the SC domain occurs in cluster 6, which is 2.3% less frequent by end-of-century. The synoptic fields for these days is depicted in Figure 11, and corresponds to a typical wind pattern from Santa Ana events (Raphael, 2003;Westerling et al, 2004;Li et al, 2016;Millstein et al, 2019;Guzman-Morales and Gershunov, 2019). The relatively high 700hPa geopotential height field over the western US, along with the high center sitting off-shore, leads to the northeasterly wind field throughout the SC region.…”
Section: Sc 6: Less Frequent and Weaker Santa Ana Winds In Fall/wintermentioning
confidence: 94%
“…The red-ish colors represent higher wind speeds and lower RH, while blue-ish colors represent lower wind speeds and higher RH controls the low-level wind patterns over SFBA. Second, they can modulate the latitudinal location of the 350-hPa Pacific jet stream, which steers the path of winter cyclones and atmospheric rivers (ARs) (Li et al 2016;Liu et al 2018;Raphael and Mills 1996). The former will be referred to as the pressure anomaly mechanism, while the latter will be referred to as the jet stream displacement mechanism.…”
Section: Individual Effectsmentioning
confidence: 99%
“…The DWs, which are a type of downslope wind, are characterized as warm, dry, and gusty northerly to northeasterly winds. They occur most frequently during the fall to early winter from the Northern Coast Ranges into the SFBA, and down the western slopes of the Sierra Nevada Mountain Range into the Great Central Valley (Li et al 2016). Occurrences of DWs are often associated with near-surface ridges that settle either along the coast of Oregon and Washington and/or over the Great Basin (Abatzoglou et al 2013;Brewer and Clements 2020;Hughes and Hall 2010;Mass and Ovens 2019), which feature a stable low-level atmosphere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In southern California, positive phases of the PDO Index are associated with higher precipitation and vice versa 22 . In this region, past studies identified the influence of the PDO on precipitation 12,24 , streamflow 13 , lake levels 25 , wind 26 , and water levels in groundwater wells 12,13 .…”
Section: Approach To Reconstruct Recharge Historymentioning
confidence: 99%